Ринок праці в Україні: сучасний стан та перспективи розвитку - Ситнік, І.В.; Горпинич, Ю.О. (Культура народов Причерноморья, 2013)
Ринок праці являє собою один з найбільш динамічних й важливих елементів ринкової економіки та є невід’ємною умовою ефективного функціонування економіки будь-якої держави. В статті досліджено становлення та розвиток ринку праці в Україні, визначено особливості впливу економічних, соціальних факторів на його формування та функціонування, розглянуто актуальні проблеми на сучасному етапі розвитку українського ринку праці, а також визначено перспективи й тенденції його подальшого розвитку. Рынок труда представляет собой один из наиболее динамичных и важных элементов рыночной экономики и является неотъемлемым условием эффективного функционирования экономики любого государства. В статье исследовано становление и развитие рынка труда в Украине, определены особенности влияния экономических, социальных факторов на его формирования и функционирование, рассмотрено актуальные проблемы на современном этапе развития украинского рынка труда, а также определены перспективы и тенденции его дальнейшего развития. In the present conditions of economic development the problems of effective employment of Ukraine, the creation of the labor market and mass unemployment are particularly urgent. The labor market is the most important among other markets. It is influenced by many factors, most of which depend on the commodity market. The market conditions depend on the state of the economy, ways of farming and structural changes, technical and organizational level of enterprises, and the quantitative and qualitative balance of the means of production and labor. But, the given human factor of production, labor market, cannot only act within certain tasks, but also it creates its own conditions for their solutions. An essential condition for the success of any economy is the availability of high-skilled competitive workforce. The labor market is one of the largest dynamic elements of a market economy, a complex system that is constantly evolving and improving. The article examines the emergence and development of the labor market in Ukraine, particularly the impact of economic and social situations in its formation and functioning. The urgent problems of modern labor market of Ukraine, and the factors that influence its functioning, income, and employment are identified and discussed. The prospects and development trends of the labor market in Ukraine are investigated.